Alternating magnetic field mediated micro reaction system for palladium-catalyzed coupling reactions. Issue 59 (27th July 2017) - Kim, Hee Jae; Choi, Jinseop; Choe, Jaehoon; Song, Kwang Ho; Lee, Sunwoo
Abstract : A continuous flow reaction system in which a palladium magnetic catalyst was immobilized and vibrated by an alternating induced magnetic field was developed. Abstract : A continuous flow reaction system in which a palladium magnetic catalyst was immobilized and vibrated by an alternating induced magnetic field was developed. The alternating electromagnetic field improved the mixing efficiency and catalytic activity for the palladium-catalyzed coupling reactions. This flow reaction system showed good product yields for various reactions such as Sonogashira, Heck, Suzuki, Stille, Hiyama and decarboxylative coupling reactions.